Examination of Huntington's disease with atypical clinical features in a Bangladeshi family tree. Issue 12 (11th November 2016) - Al‐Mamun, Md Mahfuz; Sarker, Suprovath Kumar; Qadri, Syeda Kashfi; Shirin, Tahmina; Mohammad, Quazi Deen; LaRocque, Regina; Karlsson, Elinor K.; Saha, Narayan; Asaduzzaman, Muhammad; Qadri, Firdausi; Mannoor, Md Kaiissar
Key Clinical Message: Atypical manifestation of Huntington's disease (HD) could inform ongoing research into HD genetic modifiers not present in the primarily European populations studied to date. This work demonstrates that expanding HD genetic testing into under‐resourced healthcare settings can benefit both local communities and ongoing research into HD etiology and new therapies. Abstract : Atypical manifestation of Huntington's disease (HD) could inform ongoing research into HD genetic modifiers not present in the primarily European populations studied to date. This work demonstrates that expanding HD genetic testing into under‐resourced healthcare settings can benefit both local communities and ongoing research into HD etiology and new therapies.